Pengaruh Kesadaran Merek, Kualitas Produk, dan Kepercayaan Merek Terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian Pelanggan Lip Cream Series H di Jakarta - Feby Fajrina; Rama Chandra (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
Purpose: This study aims to determine the effect of brand awareness, product quality, brand trust on customer satisfaction through purchasing decisions on H lip cream series customers in Jakarta. Methods: This research uses a quantitative approach with data collection using questionnaires and interviews of part of the questionnaire. The population in this study are customers who have bought more than once H lip cream series products and live in Jakarta with a sample size of 100 respondents using purposive sampling method. The data analysis technique used is descriptive statistics and path analysis with the help of SmartPLS 3.0 software. Result: The results prove that brand awareness, product quality, and brand trust have a direct effect on purchasing decisions. Brand awareness and brand trust have a direct effect on customer satisfaction. Meanwhile, purchasing decisions have no direct effect on customer satisfaction. Furthermore, purchasing decisions do not mediate brand awareness, product quality, and brand trust on customer satisfaction. Implication: The results of this study focus on the marketing strategy of the importance of strengthening brand awareness and brand trust in creating satisfied customers rather than just focusing on encouraging purchases.